SAÚDE DA FAMÍLIA – IMPACTO NO MODO DE ATENÇÃO E NOS INDICADORES DE SAÚDE - KOPF, ÁGUIDA W.; SAND, ISABEL C. P. V. D.; FRANZ, LIGIA B. B.; BUSNELLO, MARISTELA B.; BARTA, RENATA L.; TUSSET, JOSIANE (Salão do Conhecimento, 2013)
Resumo